Studies on passive flexible protection to resist landslides caused by the May 12, 2008, Wenchuan earthquake. (25th April 2017) - Liu, Chengqing; Wei, Xiaodan; Lu, Zheng; Wu, Handan; Yang, Yuling; Chen, Linya
Summary: The landslides caused by the 5.12 Wenchuan earthquake resulted in enormous casualties and property losses. Since the earthquake, more than 3, 600 landslides have occurred, and 17 of them were catastrophic, each of which has killed more than 30 people. Meanwhile, passive flexible protection has gradually been introduced to resist landslides due to its significant advantages of economy, safety, and environmental protection. To resist landslides effectively, it is necessary to study the load path and design method of passive flexible protection under the action of landslides. In the design of passive flexible protection against landslides, determination of the landslide load is the primary task. In this paper, the formulas of the probability density function and distribution function of the landslide pressure are developed to obtain the value of the accumulated landslide pressure acting on the passive flexible protection, which can be used as the load input parameter in the design of passive flexible protection to resist landslides. Based on the case of the "Shiziliang" potential landslide for the 5.12 earthquake, the pressure data of the landslide are collected, the calculation formulas of the volume, and the pressure of the intercepted landslide are established, and the statistical parameters of the landslide pressure‐loading sample are obtained. According to the Kolmogorov–Smirnov test method, the loading sample of the landslide pressure obeys an extreme‐value type‐I distribution, and then the load model of the landslide pressure is determined. Based on the reliability analysis method, the standard value of the landslide pressure with an over‐95% assurance rate is obtained. These results can provide references for load confirmation to design the passive flexible protection to resist landslides.